The unresolved phylogenomic tree of butterflies and moths (Lepidoptera): Assessing the potential causes and consequences. (19th March 2022) - Rota, Jadranka; Twort, Victoria; Chiocchio, Andrea; Peña, Carlos; Wheat, Christopher W.; Kaila, Lauri; Wahlberg, Niklas
Abstract: The field of molecular phylogenetics is being revolutionized with next‐generation sequencing technologies making it possible to sequence large numbers of genomes for non‐model organisms ushering us into the era of phylogenomics. The current challenge is no longer how to get enough data, but rather how to analyse the data and how to assess the support for the inferred phylogeny. Here, we focus on one of the largest animal groups on the planet – butterflies and moths (order Lepidoptera), whose phylogeny remains unresolved despite several recent phylogenomic studies. In this study, we assess the potential causes and consequences of the conflicting phylogenetic hypotheses. With a dataset consisting of 331 protein‐coding genes and the alignment length over 290, 000 base pairs, including 200 taxa representing 83% of lepidopteran superfamilies, we compare phylogenetic hypotheses inferred from amino acid and nucleotide alignments. The resulting two phylogenies are discordant, especially with respect to the placement of the superfamily Gelechioidea, which is likely due to compositional bias and possible other model violations. Furthermore, we employed a series of analyses to dissect our dataset and demonstrate that there is sufficient phylogenetic signal to resolve much – but not all – of the lepidopteran tree of life. The relationships among superfamilies within Ditrysia, the most species rich lepidopteran clade containing 98% of the extant species, remain poorly resolved. We conclude that taxon sampling remains an issue even in phylogenomic analyses and recommend that poorly sampled highly diverse groups, such as Gelechioidea in Lepidoptera, should receive extra attention in the future. Abstract : Phylogenomics has helped us resolve much of the Lepidoptera tree of life, but the relationships among the superfamilies within Ditrysia, containing 98% of the order's species richness, remain unresolved. One of the unresolved questions is the phylogenetic position of the large microlepidopteran superfamily Gelechioidea, whose placement depends on the type of data analysed, amino acids or nucleotides. The likely reason for this discordance is model violation in phylogenetic inference.